EXTH-04. ELUCIDATING THE PLEIOTROPIC EFFECTS OF VERTEPORFIN PHOTODYNAMIC THERAPY IN PRECLINICAL GLIOBLASTOMA MODELS. (12th November 2021) - Price, Gabrielle; Sudhir, Sweta; Brusco, Concetta; Bouras, Alexandros; Tsankova, Nadejda; Hadjipanayis, Constantinos
Abstract: Glioblastoma (GBM) has the highest mortality rate, incidence, and therapy resistance of all primary brain tumors. Deregulation of the epidermal growth factor receptor (EGFR) has been implicated in GBM tumorigenesis. The expression of EGFR has been linked to hippo pathway transcriptional co-activators YAP and TAZ that bind to TEAD co-factors to drive the transcription of target genes. The convergence of EGFR signaling and the hippo pathway regulates stem cell programs, including proliferation, survival, and self-renewal. Verteporfin (VP), is an FDA-approved drug for photodynamic therapy (PDT) of macular degeneration. VP has been shown to have antitumor effects both in vitro and in vivo in GBM preclinical models. As a porphyrin derivative, VP can also exert therapeutic and photodynamic effects in the presence of 689 nm light; however, the efficacy of VP-PDT has not been explored in GBM. Our results indicate for the first time that VP-PDT reduces GBM cell viability to a greater extent than VP treatment alone (viability — 0.7 uM VP: 97%, 0.7 uM VP-PDT: 46%). The antitumor effects of VP-PDT are two pronged involving 1) inhibition of live cell dynamics, including migration and intravasation, by downregulating hippo pathway constituents YAP, TAZ and TEAD and transcriptional target EGFR and 2) induction of programmed cell death by reactive oxygen species. Our results suggest that VP-PDT can be a potential avenue for treating these incurable tumors.